Upaya Pemerintah Desa dalam Meningkatkan Status Desa menuju Desa Mandiri (Studi Desa Miau Baru Kecamatan Kongbeng Kabupaten Kutai Timur) - Anjelita; Budiman Budiman; Jumansyah Jumansyah (Journal Social Politica, 2020)
The purpose of this study is to investigate how the village government efforts to improve the status of the village to become an independent village in Miau Baru Village, Kongbeng District, East Kutai Regency. Data analysis used in this study is descriptive qualitative which aims to describe and analyze each of the variables studied. Data collection techniques in this study were obtained by using purposive sampling and accidental sampling techniques. The results showed that based on the readiness of each of the efforts made by the Miau Baru Village Government, it was not optimal to improve the status of the village to become an independent village. Each of these efforts has a relationship that influences each other in taking steps as an effort to improve the status of the village towards an independent village. These efforts include 1) Organizational Capacity Efforts; 2) Program Planning and Implementation Efforts; 3) Efforts to Availability of Resources and; 4) Institutional Efforts. The inhibiting factors come in terms of budget and human resources as well as the support for good collaboration between village governments, the potential for local culture and adequate natural resources.